Programme and performance budgeting - Handa, K. L. (New Delhi, 1979)
The book has defined properly the concepts of programme and perfor mance budgeting using the relevant analytical tool of cost-benefit analy sis. Its outstanding feature is that it imparts clarity to the scope of the techniques.
Keywords: Budget